2010
DOI: 10.1136/gut.2010.213108
|View full text |Cite
|
Sign up to set email alerts
|

The mast cell stabiliser ketotifen decreases visceral hypersensitivity and improves intestinal symptoms in patients with irritable bowel syndrome

Abstract: The mast cell stabiliser ketotifen decreases visceral hypersensitivity and improves intestinal symptoms in patients with irritable bowel syndrome Klooker, T.K.; Braak, B.; Koopman, K.E.; Welting, O.; Wouters, M.M.; van der Heide, S.; Schemann, M.; Bischoff, S.C.; van den Wijngaard, R.M.; Boeckxstaens, G.E. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
294
1
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(332 citation statements)
references
References 40 publications
12
294
1
9
Order By: Relevance
“…5 Moreover, therapies targeting mast cells, such as mast cell stabilizers (cromoglycate and ketotifen) and antagonists of histamine and serotonin receptors, have been tried in IBS patients in several studies, and partially exhibited good efficacy in symptom improvement. 6,7 It further supported the key role of MCs in the process of IBS. In this review, it discussed the mechanisms of MCs in the gut dysfunctions of IBS.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…5 Moreover, therapies targeting mast cells, such as mast cell stabilizers (cromoglycate and ketotifen) and antagonists of histamine and serotonin receptors, have been tried in IBS patients in several studies, and partially exhibited good efficacy in symptom improvement. 6,7 It further supported the key role of MCs in the process of IBS. In this review, it discussed the mechanisms of MCs in the gut dysfunctions of IBS.…”
Section: Introductionmentioning
confidence: 72%
“…6 A placebocontrolled trail in 60 IBS patients showed that 8 weeks of treatment with ketotifen obviously increased the threshold for discomfort in IBS patients with visceral hypersensitivity, reduced IBS symptoms, and improved the health-related quality of life. 7 Furthermore, a prior study of 120 D-IBS patients with one or more food intolerance indicated that dietary exclusion along with oral DSCG was effective in these patients, and had a prolonged symptomatic benefit. 6 However, these studies had several limitations, such as poor design, small sample size, and selection bias.…”
Section: Mast Cells As Potential Therapeutic Target For Irritable Bowmentioning
confidence: 99%
“…Ketotifen, a mast cell stabilizer and an H1 receptor antagonist, improved IBS symptoms and quality of life [37]. This study performed in human reinforced the possibility of the use of mast cell stabilizers as a therapeutic approach in the treatment of patients with IBS [37].…”
Section: Implication Of Protease-activated Receptors In Visceral Painmentioning
confidence: 88%
“…These supernatants were characterized by an increase in tryptase, histamine and PGE 2 concentration compared to healthy control [36]. Ketotifen, a mast cell stabilizer and an H1 receptor antagonist, improved IBS symptoms and quality of life [37]. This study performed in human reinforced the possibility of the use of mast cell stabilizers as a therapeutic approach in the treatment of patients with IBS [37].…”
Section: Implication Of Protease-activated Receptors In Visceral Painmentioning
confidence: 99%
“…Th ey also suggest that cysteine as well as serine proteases may be involved in this process -an interesting fi nding given the presence of cysteine proteases in intestinal cells other than mast cells, the dominant source of serine proteases. Th e role of mast cells in IBS has been the subject of considerable interest and, although some have reported increased mast cell numbers and / or activation in IBS ( 22 -25 ), this fi nding has not been universal ( 26,27 ). Th e observation that proteases other than those derived from mast cells could be involved in neuronal eff ects mediated by IBS supernatants is an important one but the possibility that these proteases could be of bacterial origin also needs to be considered ( 28 ).…”
mentioning
confidence: 99%